Habitat area and local habitat conditions outweigh fragmentation effects on insect communities in vineyards. Issue 1 (8th January 2023) - Bosco, Laura; Moser, Valentin; Jones, Mirkka M.; Opedal, Øystein; Ovaskainen, Otso; Sonja, Gerber; Van Klink, Roel; Cushman, Samuel A.; Arlettaz, Raphaël; Jacot, Alain
Abstract: Fragmentation of habitat, for example by intensive agricultural practices, can be detrimental to local biodiversity. However, it often remains unclear whether such biodiversity declines are caused by loss of habitat area or increased fragmentation, and how habitat quality factors into it. In our study system, vegetated vineyards are typically small, and isolated from one another, potentially limiting the distribution and dispersal of organisms. In a full‐factorial experiment of a priori selected vegetated vineyard patches of differing size and fragmentation, we aimed to disentangle the effects of habitat area (area of vegetated vineyards), habitat fragmentation (number of vegetated vineyards per 100 ha) and field‐scale ground vegetation density on ground beetle, leafhopper and wild bee communities using a combined framework of multiscale and multispecies modelling (Hierarchical Model of Species Communities). We demonstrate variable effects of habitat area, fragmentation and local ground vegetation density on the three insect groups: Increased habitat area at fine scales favours higher species richness of leafhoppers, while local vegetation density boosts species richness of both leafhoppers and ground beetles, whereas no community‐level responses were detected for wild bees. We conclude that increased ground vegetation density at both field and landscape scales (i.e. higher habitat area) favours more diverse and abundant insect communities, while fragmentation effects are highly variable and species specific. In addition, our results highlight that mainly ground beetles and leafhoppers will benefit from simple ground greening measures in vineyards, while for wild bees environmental factors other than the ones tested here may drive community structure. We recommend increasing the number and area of vegetated vineyards (even at small spatial scales) requiring more nature‐friendly farming practices especially regarding a reduction or renunciation from herbicide applications, while the within‐field vegetation density should optimally be intermediate or high to favour a diverse insect community. Abstract : In our semi‐experimental study on vineyard insect communities, we investigated the effects of habitat area, fragmentation and ground vegetation density using a multiscale framework and Joint Species Distribution Modeling (JSDM). We demonstrate that increased habitat area of vegetated vineyards at fine scales favours higher leafhopper species richness, while local vegetation density boosts both species richness of leafhoppers and ground beetles. ZUSAMMENFASSUNG: Die Zersiedelung der Landschaft, beispielsweise durch intensive Landwirtschaftsnutzung, kann für die Biodiversität verheerende Folgen haben. Dennoch ist es oft unklar, ob solche Biodiversitätsverluste durch eine Abnahme der Habitatsfläche oder durch eine erhöhte Fragmentierung verursacht werden – und welche Rolle dabei die Habitatsqualität spielt. In unserem untersuchten Gebiet sind begrünte Rebberge typischerweise klein und isoliert voneinander, was potenziell die Verbreitung und Vernetzung von Organismen limitiert. In einem faktoriellen Experiment haben wir begrünte Weinparzellen mit unterschiedlicher Fläche und Fragmentierung a priori ausgewählt, um die Effekte der Habitatsfläche (Fläche begrünter Reben), Fragmentierung (Anzahl einzelner begrünter Rebflächen) und Dichte der Bodenbegrünung auf Laufkäfer, Zikaden und Wildbienen zu studieren. Wir benutzten dazu eine Kombination aus "Multiscale" (d.h. mehrere räumliche Maßstäbe) und multi‐Arten Modellierungen (Hierarchical Model of Species Communities, HMSC). Wir zeigen unterschiedliche Effekte von Habitatsfläche, Fragmentierung und Begrünungsdichte auf die drei Insektengruppen: Eine zunehmende Habitatsfläche auf kleinem Raum begünstigt eine höhere Artenvielfalt der Zikaden, wobei die Begrünungsdichte für die Artenvielfalt von Zikaden und Laufkäfern entscheidend ist. Für Wildbienen haben wir keine Multi‐Arten Effekte entdeckt. Wir schlussfolgern, dass eine erhöhte Begrünungsdichte sowohl innerhalb der Parzellen als auch auf Landschaftsebene (d.h. erhöhte Habitatsfläche) die Insektenvielfalt und ‐dichte erhöht, wobei Fragmentierungseffekte variabel und artspezifisch sind. Zusätzlich zeigen unsere Ergebnisse, dass hauptsächlich Laufkäfer und Zikaden von solchen Begrünungs‐Maßnahmen in Weinbergen profitieren, wobei für Wildbienen wohl andere Umweltfaktoren als die hier getesteten deren Vielfalt und Struktur beeinflussen. Wir empfehlen die Anzahl und die Fläche an begrünten Weinbergen zu erhöhen, was eine naturfreundliche Bewirtschaftungsweise erfordert – insbesondere bezüglich einer Reduktion oder eines Verzichts auf Herbizid‐Anwendungen. Die Begrünungsdichte innerhalb der Parzellen sollte idealerweise intermediär oder höher sein, um eine höhere Insektenvielfalt zu unterstützen.